Numerical method for bed load discharge estimation. (October 2018) - Wang, X H; Sui, H Y; Cheng, W; Gong, L Y; Yang, L
Abstract: This paper put forward a new method to estimate the bed load discharge through numerical model of bed load. Based on the concept of none-equilibrium bed load discharge, using numerical model and reverse problem solving approach through numerical simulation, this paper estimated the bed load transportation rate of the riverbed. A numerical model that can describe none-uniform and none equilibrium bed load transportation was developed in this paper. The model can simulate the hydraulic factors, Manning coefficient, bed load transportation rate, and the change of bed sediment graduation with the change of the time. Through the solution of the flow continuous equation, flow momentum equation, resistance equation, none-equilibrium bed load transportation equation and the sediment mass continuous equation, the deformation of the river bed is obtained. This model is applied to rivers with the following features: the gravel-cobble bed with sand, the little effect of the suspended sediment on the deformation of the river bed, the depth and width of none-uniform flow along the river. The model was verified by a set of flume experiment of none-equilibrium bed load discharge. The results indicate that the observed bed load transportation rate is consistent with the computational one. The results of the computing bed sediment gradation reflect the phenomenon that the scour and silting cause the larger of the bed sediment correctly. This model was applied to the estimation of bed load discharge of Changma Reservoir near the dam site, and estimate that the ratio of bed loads to suspended load 14%, which is very close to 16%–the estimation of the physical model experiment.